2007
DOI: 10.1590/s0102-311x2007000500008
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis associadas ao câncer de mama em usuárias de unidades básicas de saúde

Abstract: An epidemiological survey in ten family health units in the municipality of Teresópolis, Rio de Janeiro State, Brazil, in 2003, investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
45

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 19 publications
2
10
0
45
Order By: Relevance
“…These data are conflicting with studies in North American countries, which showed that taller women have higher risk of developing breast cancer 23 . In Brazil, considering the population of the south / southeast, in some studies height did not influence the risk for breast cancer 7,24 .…”
Section: Martins Martins Martins Martinsmentioning
confidence: 99%
“…These data are conflicting with studies in North American countries, which showed that taller women have higher risk of developing breast cancer 23 . In Brazil, considering the population of the south / southeast, in some studies height did not influence the risk for breast cancer 7,24 .…”
Section: Martins Martins Martins Martinsmentioning
confidence: 99%
“…Em relação à menarca, a frequência encontrada foi compatível com a de outro estudo realizado em Teresópolis (RJ), correspondendo a 23,4% 8 . O risco parece ser mais elevado em meninas que tiveram a menarca aos 16 anos, quando comparadas com aquelas que apresentaram 2 a 5 anos mais precocemente, e estas revelaram maiores riscos (de 10 a 30%) de desenvolverem câncer de mama 9 .…”
Section: Discussionunclassified
“…A abordagem adotada pelo programa é o oferecimento do exame citopatológico e do tratamento ou acompanhamento das lesões detectadas. 4 Apesar dessa iniciativa, os resultados não têm sido satisfatórios, pois as taxas de mortalidade por esse tipo de câncer continuam moderadamente altas no País e, do ponto de vista temporal, vem-se mantendo estáveis. 5 Uma explicação para esse resultado pode ser a não adesão das mulheres ao exame preventivo.…”
Section: Introductionunclassified